Outsiders at Medical School: Indigenous experiences in medical courses at Brazilian federal universities - Luna, Willian Fernandes; Paladino, Mariana; Cyrino, Eliana Goldfarb [UNESP] (FapUNIFESP (SciELO), 2024)
In recent decades, affirmative actions have enabled Indigenous people to access medical school, historically occupied by white people with high family incomes. This research analyzed experiences of otherness by Indigenous people in federal medical schools. This qualitative, exploratory study adopted interviews and conversation circles, with the participation of 40 students from 15 courses. We established four categories of analysis: encounter between “strangers” and the medical school; differences and inequalities; relationships with students and teachers; and conflicts and transformations. We noticed that medical schools are unwelcoming to Indigenous people, with racism, intole-rance, and tutelage, when their differences become inequalities, resulting from structural processes in these Brazilian institutions. The Indigenous presence in medical courses reveals social inequalities, causes conflicts, and initial trans-formations, pointing out paths for plurality and social justice, and possibilities for medical education with visibility and actions for the health of Indigenous peoples.
“Extraños” en la Facultad de Medicina: experiencias indígenas en las carreras de medicina de las universidades federales brasileñas
“Estranhos” na Escola Médica: experiências indígenas em cursos de medicina de universidades federais brasileiras
Keywords: Health Disparate Minority and Vulnerable Populations; Health of Indigenous Peoples; Indigenous Peoples; Medical Education; Public Policy